Street food - Choo, Jonathan Peter Xing Quan (2016)
Street Food is an animated short that tells a story of compassion and of learning to empathize with the circumstances of another. The film seeks to show how the protagonist Felipe, who is constantly harassed by a puppy stealing his food, learn the true meaning behind the puppy’s actions. That one must look beyond the actions of another and not make assumptions or judgements, especially so when one is aware of another’s circumstance. To ensure that the main points of the story are appreciated, much time was spent crafting and refining the story itself, for the animation means nothing if not for a polished story.